EFEKTIFITAS PENGELOLAAN ZAKAT DI BAITUL MAL BENER MERIAH - Bengi, Yuni Simah; Mutia, Evi; Fitri, Meutia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This research had a purpose to evaluate Baitul mal regulation in bener meriah. It is used both primary data such as interview with narasumber they are the staff of Baitul maal in bener meriah and documentary data in the Baitul mal bener meriah and secondary data such as financial data in Baitul mal bener meriah. The purpose of this research is to know how the Baitul mal in bener meriah doing the activity and operasional and is it follow the regulation that government state. It is a qualitative research with interactive analysis method such as collecting data, reducting data, verivication data and got the result to examine the problem. This research had a result such as The level of effectiveness in distributing zakat funds for 5 years is in the Very Ineffective category (ACR20%). The level of effectiveness of the distribution of zakat funds for 5 years is in the Very Ineffective category (ACR20%) and The effectiveness of zakat management starts from the Management of Biatu Mall, Bener Meriah Regency, which distributes zakat once a year, but if there is a situation of urgency, the distribution of zakat funds can be carried out before the due date for the distribution of zakat funds.